Synthesis and Structural Characterization of a Novel Carboxy-Functionalized Diiron Dithiolate Complex - Zhao, Pei-Hua; Liu, Ya-Qing; Li, Xin-ang (Asian Journal of Chemistry, 2013)
A novel carboxy-functionalized diiron dithiolate complex, [(μ-SCH2)2NCH2CH2CO2CH2CH2Cl][Fe2(CO)6] (I) as active site model of [FeFe]-hydrogenase, has been successfully synthesized by condensation reaction of [(μ-SCH2)2NCH2CH2CO2H][Fe2(CO)6] (A) with HOCH2CH2Cl in the presence of 4-dimethylaminopyridine and dicyclohexylcarbodiimide. Its structure was characterized by combustion analysis, ESI-MS, IR and 1H (13C) NMR spectroscopic techniques.